The impact of financial literacy on saving behavior among gen Y in Sabah - Aslinah Norbinsah (2016)
The purpose of this study is to explore and extent the important of financial literacy for Saving behavior among Gen Y . Awareness in Saving Plan among Gen Y is still a vague issue among society in Malaysia . Therefore, this study aimed at discussion on the impact of financial risk tolerance on the relationship between financial, literacy, demographic factors towards Saving Behavior. By using self-administered questionnaires data in relation to financial literacy divide into three which is Basic Financial Knowledge , Basic Financial Literacy and Advance Financial Literacy (independent variable), financial risk (independent variable), demographic factors (independent variable) and saving behaviour (Dependent Variable) of 123 data were collected. Smart Partial Least Square version 2.0 program was used to access the measurement model such as Convergent Validity, Reliability and Discriminant Validity as well as for structural model for hypotheses testing.The results led to main conclusion that is Advance financial literacy have a positive and significant effect Saving Behavior among Gen Y. The results of the present study are in line with earlier research indicating that financial literacy is an indicator for Saving Behavior (Lusardi and Mitchell,2007c,2009; van Rooij et al.,2011a). Thus, it is important that those who display higher in financial literacy are more likely to prepare for their Saving by accumulating more wealth.